Адыги на Нижнем Дону (относительно первого упоминания о касогах в древнерусских летописях) - Бубенок, О.Б. (Боспорские исследования, 2009)
The hypothesis gains ground among contemporary scientists according to which Adygei tribes known as the «Zykhes» among Byzantines and the «Kasogs» or «Kashaks» among the other peoples lived in North-Western and Western Caucasus in Khazar period, at the close of the 7th century - the 10th century AD. Moslem and Byzantine authors’ data give such grounds. The author draws the conclusion that the data from excavations of Borisov cemetery at North-Western Caucasus and Artuganov cemetery in the Lower Don region as well as the information from the «Narrative chronicle» about the events of 965 give evidences to suppose that not only the Alans and the Bulgars but also one of the tribes of the Zykhes-Kasogs that were subjects of the Khazarian empire were resettled from North Caucasus to the Don region by the Khazars in the first half of the 8th century.